From Biology to Clinical Practice: Iron Chelation Therapy With Deferasirox - Palumbo, Giuseppe A.; Galimberti, Sara; Barcellini, Wilma; Cilloni, Daniela; Di Renzo, Nicola; Elli, Elena Maria; Finelli, Carlo; Maurillo, Luca; Ricco, Alessandra; Musto, Pellegrino; Russo, Rodolfo; Latagliata, Roberto (Frontiers in Oncology, 2021)
Iron chelation therapy (ICT) has become a mainstay in heavily transfused hematological patients, with the aim to reduce iron overload (IOL) and prevent organ damage. This therapeutic approach is already widely used in thalassemic patients and in low-risk Myelodysplastic Syndrome (MDS) patients. More recently, ICT has been proposed for high-risk MDS, especially when an allogeneic bone marrow transplantation has been planned. Furthermore, other hematological and hereditary disorders, characterized by considerable transfusion support to manage anemia, could benefit from this therapy. Meanwhile, data accumulated on how iron toxicity could exacerbate anemia and other clinical comorbidities due to oxidative stress radical oxygen species (ROS) mediated by free iron species. Taking all into consideration, together with the availability of approved oral iron chelators, we envision a larger use of ICT in the near future. The aim of this review is to better identify those non-thalassemic patients who can benefit from ICT and give practical tips for management of this therapeutic strategy.